2021
DOI: 10.1007/s00167-021-06634-4
|View full text |Cite
|
Sign up to set email alerts
|

Both arthroscopic and open posterior knee capsulotomy are effective in terms of extension recovery and functional improvement—systematic review

Abstract: Purpose To assess the recovery of extension and improvement in functional scores after an arthroscopic or open posterior knee capsulotomy in the setting of an extension deicit. Methods A systematic search of articles published between 1980 and 2020 was performed in the MEDLINE/PubMed database, EMBASE/Ovid database and Web of Science database. The inclusion criteria consisted of patients with primary extension deicits > 5° who underwent an arthroscopic or open posterior knee capsulotomy. The assessed outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Medial soft tissue release demands strict control to achieve proper soft tissue mediolateral balance in flexion and extension in patients with medial stabilized implants for varus deformity. Soft tissue release techniques result in slightly different outcomes [3,11]. Previous clinical research revealed that the superficial MCL release effect was significantly greater in flexion than in extension during posteriorstabilized TKA [2].…”
Section: Discussionmentioning
confidence: 99%
“…Medial soft tissue release demands strict control to achieve proper soft tissue mediolateral balance in flexion and extension in patients with medial stabilized implants for varus deformity. Soft tissue release techniques result in slightly different outcomes [3,11]. Previous clinical research revealed that the superficial MCL release effect was significantly greater in flexion than in extension during posteriorstabilized TKA [2].…”
Section: Discussionmentioning
confidence: 99%
“…However, we are not aware of a different treatment modality other than posterior knee capsulotomy that is effective in the treatment of knee extension deficit refractory to guided physiotherapy and thorough joint arthrolysis. 3 , 10 It was therefore considered unethical to leave a control group with no treatment due to the highly debilitating nature of the disease. 1 , 2 , 5 Further, the study group was relatively heterogeneous, especially in comparison with previous works.…”
Section: Discussionmentioning
confidence: 99%
“…In such rare cases, the treatment consists of a posterior capsulotomy (posterior capsular release) of the affected joint. 3,7,10,16 Traditionally, this procedure has usually been performed through an open approach. 8,9,12,16 An arthroscopic approach is a less invasive procedure, 14,18 potentially resulting in limited postoperative pain, 14,18 faster recovery, 7,14,18 and increased postoperative function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among such procedures are removal of posterior pathologic findings (i.e., loose bodies, tumors, cysts), PCL reconstruction and repair, repair of the posterior meniscal horns, and posterior capsular release for extension contracture. 1 , 4 , 6 , 8 , 9 , 10 , 11 , 12 , 13 …”
mentioning
confidence: 99%